Kepemimpinan Kreatif dan Kinerja Teknologi Informasi: Studi Kasus Penggunaan EMR dalam Manajemen Pendidikan Rumah Sakit (Jurnal Sosial Humaniora dan Pendidikan, 2025)
Digital transformation in the health sector requires an innovative and adaptive information management system, one of which is through the implementation of Electronic Medical Record (EMR). This study aims to evaluate the role of creativity and innovation management in improving the performance of EMR use at Hermina Manado Hospital. The research approach used was descriptive quantitative, with data collection techniques through online questionnaires to 24 medical personnel as respondents. The research instrument was tested for validity and reliability, resulting in a Cronbach's Alpha value of 0.891. Data were analyzed using a single-sample t-test and one-way ANOVA. The results showed that all dimenimplementingsions of EMR use—including efficiency and productivity, quality of service, comfort and ease of use, organizational satisfaction, and support for creativity and innovation—obtained a satisfaction score above 88%, with the comfort category reaching the highest score. All categories showed significant differences from the theoretical mid-scale (p < 0.05), and there was a significant difference between categories (p = 0.0351). These findings confirm that the success of EMR implementation is heavily influenced by managerial strategies that encourage innovation and creativity, not just by technological factors. This research makes an empirical contribution to the study of health information systems and underlines the importance of integrating innovative cultures in hospital digitalization policies. The practical implications of this study lead to the importance of ongoing training, user-friendly system design, and participatory-based performance evaluation.